Politeness Strategies Used by Teenage Characters in Stranger Things Movie Series: A Pragmatics Study - Samia Salsabila; Dwi Rahayu (UM Purwokerto Press, 2023)
This study aims to identify any kinds of politeness strategies used by teenagers in Stranger Things movie and also to describe the factors influencing the teenage characters’ choice of politeness strategies in Stranger Things movie. The writer uses a descriptive qualitative method to explain the data and follows the theory of Brown and Levinson (1987) to answer the statement of the problem. This study found 38 data in total consisting of 6 bald on record, 25 positive politeness, 4 negative politeness, and 3 off-record. Other than that, there are also 22 data that are influenced by social distance, 4 data that are influenced by relative power, and 12 data that are influenced by rank of imposition. The result of this study shows that teenage characters tend to use positive politeness strategies when they communicate with other people. Moreover, social distance is the most the factor that influences teenage characters to use politeness strategies. It can be concluded that the typical teenagers in Stranger Things movie are easy to get along with because they try to make themselves close with the interlocutor when they have a conversation, and they know how to socialize well by understanding and appreciating people’s opinions.